ATTITUDE TOWARDS USING ICT IN LEARNING AND TEACHING MATHEMATICS - Takahashi, Arita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
This study questions attitudes of students and mathematics teachers towards using ICT in state schools of Latvia. The author has been using Latvian education portal “uzdevumi.lv” in teaching of mathematics for several years and has observed a very wide acceptance of this learning tool both among children and teachers. On the other hand, there have been certain obstacles to apply this and other ICTs more widely. Other sites, such as “Geogebra” and “Brilliant” have been used by schools abroad. The author observes that the things that prevent schools from using such sites to a large degree depend not only from the availability of computers at school, but also from students and teachers attitudes towards using ICT in mathematics learning and teaching.